Archaeology and geographic information systems
1 online resource (320 pages)
Keywords: Geographic information systems GIS applications are viewed with increasing interest by the archaeology community and this book, with its diversity of topics and authorship, should be a useful resource. Complementing the volume "Interpreting Space" Taylor & Francis, 1990, which focused on North American archaeology, this title further develops themes within a specifically - though not exclusively - European context.; It is apparent that there are fundamental differences between North American and European archaeological uses of GIS. Primarily these differences lie in the types of evidence for past landscapes that are available for study in the two continents, and secondly in the different approaches to archaeology and specifically the theory and practice of landscape archaeology. This title centres on the role of archaeological theory in cultural resource management CRM and in GIS applications generally. It showcases the important debate which takes the emphasis away from the technology of GIS and places it back within the central concerns of archaeology and particularly European archaeology.; "Archaeology and GIS" includes material on such concerns as CRM applications, landscape archaeology, intra-site applications and explicitly theoretical concerns, thus representing the state of GIS applications in European archaeology. Contributions come from countries such as France, Italy, Hungary, UK, USA, the Netherlands, the Czech Republic, Spain, Slovenia and Finland